Distribution of ESBL-producing and non-ESBL-producing Klebsiella pneumoniae isolated from sputum specimens in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia - SUHARTONO SUHARTONO; ZINATUL HAYATI; WILDA MAHDANI; FIRA ANDINI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suhartono S, Hayati Z, Mahdani W, Andini F. 2024. Distribution of ESBL-Producing and Non-ESBL-Producing Klebsiella pneumoniae isolated from sputum specimens in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia. Biodiversitas 25: 3247-3254. Klebsiella pneumoniae, a significant nosocomial pathogen, particularly in the case of strains producing extended-spectrum beta-lactamase (ESBL), was the focus of this study. The study aimed to determine the distributions stratified by patients’ age, sex, hospital wards, and the antimicrobial susceptibility pattern of ESBL and non-ESBL K. pneumoniae isolated from expectorate sputum at Zainoel Abidin General Hospital (RSUD dr. Zainoel Abidin), Banda Aceh, Indonesia, from January 2021 to January 2024. The prevalence of ESBL-producing K. pneumoniae was 79.84% (103/129 isolates), with the highest incidence found in patients aged >45 years (74.76%) and males (67.96%). The prevalence of non-ESBL-producing K. pneumoniae was 20.16% (26 isolates), with the highest incidence in patients aged >45 years (76.92%) and males (62.23%). The surgical ward had the highest incidence of ESBL-producing K. pneumoniae (14.56%), followed by the cardiopulmonary ward (14.56%). The cardiopulmonary ward also had the highest incidence of non-ESBL-producing K. pneumoniae (38.47%). The ESBL-producing K. pneumoniae isolates were more sensitive to amikacin than non-ESBL isolates, while the non-ESBL-producing K. pneumoniae isolates were sensitive to cefotaxime, amikacin, and tobramycin. The increasing prevalence of ESBL-producing K. pneumoniae underscores the significance of the study's findings, providing valuable insights into the epidemiology and antibiotic susceptibility profiles of K. pneumoniae in this clinical setting and the importance of reasonable antibiotic use.